Frei, fair und lebendig – Die Macht der Commons - Helfrich, Silke; Bollier, David (transcript, 2020)
This book is meant to encourage. It unites relational thinking with a new way of acting. The goal: a free, fair and vibrant society. But what we are used to is deeply rooted in our minds, in our everyday lives, in the market and the state. Silke Helfrich and David Bollier uncover traditional patterns of thought and design a program for a successful cooperation, a different political understanding and a caring economy. They focus on practices, showing how we pursue common goals in diversity. In practice, houses and vehicles can be built in a similar way to Wikipedia. The book also encourages us to think like a »Commoner«. It offers a language for the world of tomorrow. It not only changes the economy and politics – it changes us.